COMMERCIALIZATION AND CONTEMPORARY DEVELOPMENT OF FOLK PAINTINGS - Baranwal, Shubhra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper is based on the commercialization of Indian folk paintings and how Indian folk paintings has gained a strong position in the world art market. The commercialization of folk painting was initiated as a preservation effort. Folk paintings was created primarily on wall and floors to worship nature and gods, but now it has become a major source of income. When art conservators visited Indian villages, they found beautiful paintings on the walls of village houses and temples. Subsequently, efforts were made to preserve them. These villagers were given art materials to make big artworks and then these art pieces were showcased in global art galleries. Result in capturing the attention of art enthusiasts and generating a demand to buy these folk paintings. For the artists, their art became their livelihood. Today, Indian folk art is witnessing a surge in popularity, with digital platforms and e-commerce playing an important role. Work is being done at the national and international levels to preserve them, which will help keep these arts alive in the future. Currently, a few folk arts have prominent place in the commercialization of art and this research study is based on the commercialization of all of these folk paintings.